Instruksi Walikota Jayapura : Effectiveness of Lawin Creating a Clean and Healthy Environment: Instruksi Walikota Jayapura: Efektivitas Hukum Instruksi Walikota Jayapura dalam Mewujudkan Lingkungan Bersih dan Sehat - Hasrifal Hasrifal; Amri Amri (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
To reduce environmental pollution from plastic waste and minimize the use of plastic bags. Thus, the Jayapura City government issued a policy of Mayor Instruction number 1 of 2019 regarding using alternative shopping bags instead of plastic bags. This study aims to find out how the application of these instructions in the community and the administrative law view of the policy on environmental pollution problems in Jayapura. Quality research will be used in this study as data collection through the review of Mayor Instruction Number 1 of 2019, interviews, and observations. The results showed that this instruction was only aimed at specific merchants, such as modern shops/stalls and supermarkets. Meanwhile, traditional market dealers and small stalls on the roadside should be applied. In practice, the shops and merchants mentioned must provide alternative bags, such as noken and cardboard, for people who shop. Confiscation sanctions will be imposed If the business actor does not provide alternative plastic bags. The subsequent finding is that the level of compliance of business actors with these instructions is high. Meanwhile, the legal hierarchy of the Administration of the Mayor of Jayapura Instruction Number 1 of 2019 is a simplified form of Law Number 32 of 2009 concerning environmental management. However, the Jayapura mayor's instruction has not been effective in environmental management. That is because there are still floods due to the accumulation of rubbish aimed at certain business actors.